Pengaruh Penambahan Tepung Daun Belimbing Wuluh (Averrhoa bilimbi L) Dan Enkapsulasi Belimbing Wuluh Sebagai Feed Additive Terhadap Performa Broiler. - Siregar, Y A; Montesqrit, M; Harnentis, H (PETERPAN (Jurnal Peternakan Terapan), 2024)
This study was conducted to determine the effect of adding Averrhoa bilimbi L leaf meal and encapsulated Averrhoa bilimbi L on the broiler performance. The material used in this study included 120 broiler chickens, Averrhoa bilimbi L leaf meal and encapsulated Averrhoa bilimbi L. The research method used was a Complete Randomized Design with 6 treatments and 4 repeats. Each repeat of this study used 5 broiler chickens. The treatment in this study consisted of P0 control (ration with antibiotics Zinc bacitracin), P1 (Averrhoa bilimbi L leaf meal 1%), P2 (Averrhoa bilimbi L leaf meal 2%), P3 (encapsulated Averrhoa bilimbi L 1%), P4 (encapsulated Averrhoa bilimbi L 2%), P5 (Averrhoa bilimbi L leaf meal 1% encapsulated Averrhoa bilimbi L 1%). The variables observed were feed intake,body weight gain, feed conversion ratio and mortality. The data obtained were then analyzed using ANOVA and if there was a significant effect continued with Duncan's Multiple Range Test. The results showed that the addition of Averrhoa bilimbi L leaf meal and encapsulated Averrhoa bilimbi L as a feed addtive antibiotic growth promoter had a real effect (P<0.05) on feed consumption but no real effect (P>0.05) on weight gain, ration conversion and mortality. The conclusion of this study was Averrhoa bilimbi L leaf meal and encapsulated Averrhoa bilimbi L can be used as 2% in diets without affecting the broiler performance.